(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the impact of integrating information and communication technologies (ICT) on the effectiveness of teacher education and classroom practices. It analyzes how ICT tools contribute to improving teacher qualifications, lesson quality, and student engagement. The study also highlights existing challenges and provides recommendations for more effective implementation.